Analysis of the thermo-fluidic transport around counter-rotating tandem circular cylinders. (April 2022) - Chatterjee, Dipankar; Chaitanya, N. V. V. Krishna; Mondal, Bittagopal
The work physically relates to the influence of thermal buoyancy on the flow and heat transfer of an incompressible fluid around two counter-rotating circular cylinders arranged in tandem configuration within an unconfined domain. Two-dimensional numerical simulations are conducted using a finite volume based computational fluid dynamics tool to explore the problem. The Reynolds number is taken as 100 with Prandtl number 0.71, keeping the non-dimensional spacing between the cylinders fixed at 1.5. The cylinder rotations are considered in the range of a dimensionless speed of 0 to 5. The upstream cylinder is rotating in the clockwise sense, whereas, the downstream one in the counter-clockwise sense. The buoyancy effect is analyzed for the Richardson number range 0 to 1. The flow is unsteady periodic characterized by vortex shedding around the stationary cylinders at the chosen value of the Reynolds number. The flow shows unsteadiness with vortex shedding initially with increasing rotational speed; however, at a critical value of the rotation, the flow becomes stabilized with suppression of vortex shedding. On the contrary, the cross thermal buoyancy effect destabilizes the flow into an unsteady periodic pattern. This complex interplay among the free stream flow, cross buoyancy, and counter-rotation produces intriguing fluid dynamic and thermal phenomena. The critical rotational speeds for the range of Richardson numbers are obtained asΩ c r = 1.1, 3.4, 3.8, 4.7 respectively for Ri  = 0, 0.25, 0.5 and 1. A corresponding regime diagram is also constructed to depict the unsteady and steady zones of operation.